PENGARUH BLANCHING TERHADAP LAJU PENGERINGAN DAN KADAR ASAM LEMAK BEBAS KOPRA (THE EFFECT OF BLANCHING ON DRYING RATE AND FREE FATTY ACID CONTENT OF COPRA) - Arifin, Miftakhul (Jurnal Ilmu-Ilmu Pertanian, 2005)
Research was conducted to study the effect of blanching on drying rate, and the free fatty acid content of copra. Blanching of copra was performed before drying. The moisture contents of copra determined before and during drying; while free fatty acids were only determined after drying. The experimental design used in the experiment was Completely Randomized Design, which consists of two factor namely the blanching periods i.e. 0; 5; 10 and 15 minutes, and the blanching methods i.e. steam blanching at atmospheric pressure and dipping in boiling water. The result shows that the blanching treatment increases the drying rate, and reduces the free fatty acid contents. Blanching time affect both water evaporation rate and free fatty acid contents, however dipping in boiling water for 15 minutes inhibit water evaporation. Steam blanching treatment at atmospheric pressure for 15 minutes on the raw materials, produces the best copra, which has the greatest drying rate and the least free fatry acid as well.